Interpretasi Peran Ayah Pada Film "Father And Son" - Pardede, Bintang; Sholihul Abidin (SCIENTIA JOURNAL, 2024)
In the film 'Father and Son' (2024), the portrayal of the father as a protector, mentor, and emotional anchor delves deeply into the intricate dynamics of father-son relationships. Through authentic emotional interactions and realistic conflicts, the movie vividly captures the profound influence fathers have in shaping their children's lives.